Pengembangan Model Pelatihan Internal (Analisis Kebutuhan, Evaluasi Aplikasi dan Pelatihan) - Harimurti, Dyah (ANIMA Indonesian Psychological Journal, 2007)
The aim of this research is to standardize training need analysis, especially for soft skill competence, and follow up the result of the need analysis with a training package. The assessment phase reveals that a systematic training need analysis could be standardized in accordance with the real problems in the company. At the intervention phase, the chosen topic was the change manage- ment as an important and urgent competence to be trained to the unit supervisors at CV. “X”. Effec- tiveness of the training was measured at reaction and learning levels. At the reaction level, the partici- pant were satisfied with the training. The learning level measured through pre- and post-tests reveals a significant enhancement of the participant’s knowledge. Tujuan penelitian ini adalah membakukan analisis kebutuhan pelatihan khususnya kompe- tensi soft skills, dan menindaklanjuti hasil analisis kebutuhan dengan memberikan suatu bentuk pela- tihan. Tahap asesmen menunjukkan training need analysis yang sistematis bisa distandardisasi sede- mikian rupa sehingga bentuk pelatihan yang diidentifikasi sesuai dengan permasalahan nyata di peru- sahaan. Tahap intervensi, memilih topik manajemen perubahan, sebagai kompetensi penting dan mendesak untuk dilatihkan pada kepala unit di CV. X. Keefektifan pelatihan diukur pada level reaksi dan level pembelajaran. Pada level reaksi, pelatihan memperoleh sambutan baik dari partisipan. Level pembelajaran diuji dengan membandingkan pre dan post-test, menunjukkan adanya peningkatan yang signifikan pada pengetahuan partisipan.